Proposed Specifiers for Conduct Disorder (PSCD): Factor Structure and Validation of the Self-Report Version in Community and Forensic Samples of Portuguese Youth. (January 2023) - Ribeiro da Silva, Diana; Sousa, Ruben; Rijo, Daniel; Mendez, Beatriz; Tsang, Siny; Salekin, Randall T.
The Proposed Specifiers for Conduct Disorder (PSCD) was developed as a measure to assess the multifaceted model of psychopathic traits in children/youth (i.e., grandiose–manipulative [GM], callous–unemotional [CU], and daring–impulsive [DI] traits) in addition to Conduct Disorder (CD) symptoms. This study aims to test the psychometric properties of the PSCD-self-report version across community ( n = 648; 52.9% female) and forensic male youth ( n = 258) from the Portuguese population. Results supported a general factor and four specific factors (GM, CU, DI, CD), which was invariant across gender and sample type. Evidence for reliability, construct, and temporal validity were also found. Overall, the PSCD appears to be a promising measure for assessing psychopathic traits in youth from both community and forensic settings, which may contribute to the discussion around the conceptualization, assessment, predictive value, and clinical usefulness of the multifaceted model of psychopathy in youthful populations, particularly in its association with CD.